Patient and clinician perceptions of telehealth in musculoskeletal physiotherapy services - A systematic review of the evidence-base. - Anthony Smith; Sue Innes (PLOS Digital Health)
Telehealth has been at the forefront of healthcare delivery since the Covid-19 pandemic with a prompt shift in transition from face-to-face delivery to remote contact. This critical review aims to understand patient and clinician views of telehealth adoption regarding effectiveness and satisfaction within musculoskeletal (MSK) physiotherapy services. A systematic process was used to search for evidence within 6 databases (CINAHL, PyscINFO, Medline, AMED, EMCARE, EMBASE) utilising clear inclusion and exclusion criteria in August 2024. Articles published in English between 2019-2024 were searched, a total of 394 articles were identified and 10 articles were included in the review. Methodological quality was evaluated using the CASP, JBI and QuADS tools. Findings were evaluated via consensus and showed clear patient and clinician satisfaction with positive themes of reduced travel, reduced physical burden, flexibility/accessibility and negative themes of reduced physical contact, computer literacy and privacy infringements. Quality analysis identified non-response bias, sampling bias, and participants mix as risks to overall validity. Telehealth has shown to be an effective and transformative model of healthcare delivery for musculoskeletal services, especially in improving access and convenience for patients. Implications for practice suggest a need for a hybrid model of care, enhanced training, and improved data security. Future research should focus on satisfaction within condition specific musculoskeletal health, overall cost-effectiveness, health equity, and the integration of advanced technologies to ensure telehealth can be a sustainable and inclusive part of the healthcare landscape moving forwards.